2021
DOI: 10.1039/d0nr08998b
|View full text |Cite
|
Sign up to set email alerts
|

Anisotropic nanoporous morphology of ZnO-supported Co that enhances catalytic activity

Abstract: A novel conversion reaction synthesis (CRS) method was used to synthesize ZnO-supported Co nanoporous metal hybrid structures from a co-precipitated nanocomposite precursor of ZnO and Co3O4. After removal of Li2O...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
4
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 42 publications
0
4
0
Order By: Relevance
“…While laboratory XRD is sufficient to determine the Suzuki phase and analyze changes during conversion, synchrotron XRD is required to fully resolve the cobalt phases in the NWs, as is shown previously on ZnO/Co nanoporous composites. 34 Lab XRD of the Co NWs only shows a broad Co peak due to the extremely small nanoscale Co domains (ESI S2 † ).…”
Section: Resultsmentioning
confidence: 99%
“…While laboratory XRD is sufficient to determine the Suzuki phase and analyze changes during conversion, synchrotron XRD is required to fully resolve the cobalt phases in the NWs, as is shown previously on ZnO/Co nanoporous composites. 34 Lab XRD of the Co NWs only shows a broad Co peak due to the extremely small nanoscale Co domains (ESI S2 † ).…”
Section: Resultsmentioning
confidence: 99%
“…Cobalt oxide is a p-type SMO, which can build a p-n junction with various n-type semiconductor materials on the contact surface to improve the response of pure inductive materials. This performance improvement is due to the mutual catalysis between Co 3 O 4 and n-type semiconductor materials [27]. However, the accumulation of cobalt nanoparticles usually occurs in actual composite synthesis, resulting in the degradation of gas sensitive properties [28].…”
Section: Introductionmentioning
confidence: 99%
“…We recently demonstrated that CRS-derived NPMs can exhibit improvements in catalytic activity relative to conventional nanoparticle metals . However, access to a wide range of particle and pore sizes is needed, as different catalysis applications have different optimal particle sizes and morphologies.…”
mentioning
confidence: 99%
“…We recently demonstrated that CRS-derived NPMs can exhibit improvements in catalytic activity relative to conventional nanoparticle metals. 22 However, access to a wide range of particle and pore sizes is needed, as different catalysis applications have different optimal particle sizes and morphologies. For example, the smallest particle sizes have the highest accessible surface areas, but larger particle sizes have better resistance to coarsening during extended use at higher temperatures.…”
mentioning
confidence: 99%